Personality of Children with Special Needs: Mentally Retarded, Deaf and Physically Disabled - Nurul Husna; Syafrul Nalus; Sasmi Nelwati (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2023)
Personality is the overall way an individual reacts and interacts with other individuals. There are several aspects that make up personality: character, attitude, and temperament. This research aims to reveal the personality of children with special needs. Through literature research and using a descriptive approach and concept analysis, the results of this research: mentally retarded children are easily swayed (easily seduced), do not have a stance, and are less attractive in appearance. personal aspects and speaking style. The nature of deaf children is egocentric. The characteristics of children with physical impairments are low self-esteem, closing themselves off from other people, and lacking self-confidence. Children with intellectual disabilities are generally aggressive, but behind that they are also more sympathetic and empathetic than normal children. Deaf children are suspicious of other people and are often impulsive. The attitudes of children with physical disabilities tend to be selfish and apathetic towards activities in society. The mentality of mentally retarded children is jealous, they can even get angry if they feel they are being bullied. Deaf children are temperamentally different from mentally retarded and physically handicapped children; their anger is directed at others. Children with physical disabilities who are temperamental often show sadness, depression, stress, rarely smile, are anxious, and sometimes irritable. The anger shown by a physically disabled child is anger at his condition being less than perfect compared to other people.